Using Computable General Equilibrium Models to Analyze Economic Benefits of Gender-Inclusive Policies - Kabir, Kayenat; Dudu, Hasan (World Bank, Washington, DC, 2020)
Computable general equilibrium (CGE) models are economy-wide simulation tools that can be very useful in answering the policy questions related to closing gender gaps. They allow us to estimate the contributions of gender-inclusive policies, quantify costs and benefits of associated reforms for policy prioritization, identify winners and losers of suggested reforms, and understand transmission channels. They also allow us to estimate distributional and sectoral impact of economy-wide shock such as the containment measures to mitigate the spread of COVID-19 (Coronavirus). This note provides a brief overview of computable general equilibrium model-based analysis in the context of gender-inclusive policies. The purpose of this note is to familiarize non-CGE modelers with this tool and advance discussion on how results derived from it can be used to aid policy dialogue and enhance the design and implementation of gender activities in operations, leading to more gender-inclusive economies and sustainable results for women on the ground. The note covers what the World Bank has been doing on this front, data requirements for such analysis, and how to chart the way forward.